2018 Power Systems Computation Conference (PSCC) 2018
DOI: 10.23919/pscc.2018.8442510
|View full text |Cite
|
Sign up to set email alerts
|

Operational Hydropower Simulation in Cascaded River Systems for Intraday Re-Planning

Abstract: In this paper, we introduce an operational implementation of a hydropower simulator for cascaded river systems. It is presently used for decision support in the intraday re-planning by the largest hydropower producer in Norway. It simulates the hydro production at a highly detailed level with very fine time resolution. The outcome obtained in one time period will be immediately used to facilitate the calculation at the next time period. The continuous updating of the information within short intervals not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…More recently, such simulations and decisionmaking in the electricity market have become more popular as the power generation systems became an integral part of the smart grid systems (Ringler et al, 2016). Whereas the previous research of Ivar Skjelbred and Kong (2018) made intraday replanning after simulating the actual operation process. The study by Aliabadi et al (2017) concluded bidding decisionmaking by simulating the bidding behaviors of generators under different market modes, such as capacity and auxiliary market.…”
Section: Figurementioning
confidence: 99%
“…More recently, such simulations and decisionmaking in the electricity market have become more popular as the power generation systems became an integral part of the smart grid systems (Ringler et al, 2016). Whereas the previous research of Ivar Skjelbred and Kong (2018) made intraday replanning after simulating the actual operation process. The study by Aliabadi et al (2017) concluded bidding decisionmaking by simulating the bidding behaviors of generators under different market modes, such as capacity and auxiliary market.…”
Section: Figurementioning
confidence: 99%
“…Concerning the RTD and related short-term hydro scheduling (STHS) problems, such as the hydro unit commitment (HUC) [10], given the necessity of accurate HPF representation, the transmission network modeling implicates in complex optimization problems. Works that deal explicitly with RTD problems in hydro plants, similar to [11]- [12], are relatively less common than those focusing on other types of STHS problems, such as the HUC. As far we know, there are no works specifically oriented at handling the hydro RTD and the ACOPF simultaneously.…”
Section: Introductionmentioning
confidence: 99%